Board hierarchy, independent directors, and firm value: Evidence from China - Zhu, Jigao; Ye, Kangtao; Tucker, Jennifer Wu; Chan, Kam (Johnny) C. (Journal of Corporate Finance, 2016)
While US companies mainly list their board of directors alphabetically, this is not the case for Chinese companies, most of which list their independent directors last. We interpret the listing order of Chinese directors as board hierarchy, reflecting power allocation within the board. Based on extant evidence that independent directors contribute to firm value and that empowered individuals have more influence in group decision making, we expect independent-director rankings to be positively associated with firm value and find evidence consistent with this prediction. In our supplementary analyses we explore the mechanisms through which empowered independent directors enhance firm value. We find that independent directors who are ranked higher are more likely to vote against the management, especially on financial reporting issues. Further, higher independent-director rankings are associated with less earnings management. Our study suggests that empowering independent directors increases firm value.